Economic Management Transformation in Maintaining the Social Economy of the Community During the Global Crisis - Fitriani Latief; Asniwati (Universitas Pendidikan Ganesha, 2026)
The low effectiveness of economic management is caused by the less-than-optimal impact of policies and the organizational environment. The urgency of this research arises because the role of MSMEs is very vital in the global economy, vital in absorbing and reducing poverty amid the global crisis, but their business continuity still faces internal obstacles. The purpose of this study is to analyse the influence of leadership and the organizational environment on the success of MSME management. The sample consisted of 371 MSME owners, selected by total sampling. Data were collected through observation, questionnaires, and documentation, then analysed using logistic regression with the help of SPSS version 29.0. The results showed that leadership had a significant effect on the success of MSMEs (B = 0.830; t = 9.834; p = 0.046) and the organizational environment was also significant (B = 0.806; t = 3.992; p = 0.001). Simultaneously, the two variables explained 73.7% (adjusted R² = 0.737) of the variation in the success of MSME management with an F value of 71.064; p < 0.001. The findings of this study confirm that effective and environmentally friendly leadership in organizations supports the health and well-being of businesses nationally and globally. The study's conclusions indicate that enhancing leadership capacity and a collaborative organizational culture are key to success in the social economy of society. The implications of this study emphasize the importance of leadership training and strengthening a work culture, including community participation.